Feasibility of post-exposure-prophylaxis with single-dose rifampicin and identification of high prevalent clusters in villages' hyperendemic for leprosy in Senegal. - Gilbert Batista; Pauline Dioussé; Papa Mamadou Diagne; Mahamat Cissé; Ibrahima Tito Tamba; Fatou Diop; Fanta Diop; Lahla Fall; Diama Sakho; Mariama Bammo; Ndiaga Guèye; Christa Kasang; et al. (Public Library of Science (PLoS), 2024)
Introduction Senegal is a leprosy low-endemic country with nine villages known to be hyperendemic with a leprosy incidence rate above 1,000 per million inhabitants. We aim to implement a door-to-door screening strategy associated with the administration of a single-dose-rifampicin (SDR) as post-exposure prophylaxis (PEP) to household and social contacts in these villages and to identify spatial clustering and assess the risk of leprosy in population according to the physical distance to the nearest index-case. Methods From October/2020 to February/2022 active door-to-door screening for leprosy was conducted in nine villages. Using an open-source application, we recorded screening results, demographic and geographic coordinate's data. Using Poisson model we analysed clustering and estimated risk of contracting leprosy in contacts according to the distance to the nearest new leprosy patient. Results In nine villages, among 9086 contacts listed, we examined 7115. Among 6554 eligible contacts, 97.8% took SDR. We found 39(0.64%) new leprosy cases among 6,124 examined in six villages. Among new cases, 21(53.8%) were children, 10(25.6%) were multibacillary and 05(12.8%) had grade 2 disability. The prevalent risk ratio and 95% confidence intervale(95%CI) adjusted by village were 4.2(95%CI 1.7-10.1), 0.97(95%CI 0.2-4.4), 0.87(95%CI 0.2-25), 0.89(95%CI 0.3-2.6) and 0.70(95%CI 0.2-2.5) for the contacts living in the same household of an index case, 1-25m, 26-50m, 51-75m and 76-100m compared to those living at more than 100m respectively. We identified nine high prevalent clusters including 27/39(69%) of new cases in 490/7,850(6%) inhabitants, with relative risks of 46.6(p-value = 0.01), and 7.3, 42.8, 8.2, 12.5, 11.4, 23.5, 22.3, and 14.6 (non-significant p-values). Conclusions Our strategy has proved the feasibility of active screening for leprosy in contacts and the introduction of PEP for leprosy under programmatic conditions. Only individuals living in the same household as the leprosy patient had a significant risk of contracting leprosy. We documented nine clusters of leprosy that could benefit from tailored control activities while optimizing resources.